Swedish Managers’ and HR-Officers’ Experiences and Perceptions of Participating in Alcohol Prevention Skills Training: A Qualitative Study - Martinez, Martina Wilson; Berglund, Kristina; Hensing, Gunnel; Sundqvist, Kristina (Frontiers in Psychology, 2022)
Objective: The objective of this study was to explore Swedish managers’ and HR-officers’ experiences and perceptions of skills training and development and implementation of an alcohol policy. Methods: Semi-structured interviews were conducted with Swedish managers (n = 44) and HR-officers (n = 9) from nine different organizations whom had received skills-training and an organizational policy implementation. The interviews were analyzed using thematic analyses. Results: In total, nine themes were identified: The prevalence of alcohol problems: a wake-up call; a reminder to intervene immediately; an altered view of the responsibility of the employer; initiating conversations about alcohol: a useful toolbox; an imprecise, yet positive, memory; increased awareness of issues related to alcohol culture; I have not heard a word about a new alcohol policy; the alcohol policy: a mere piece of paper; alcohol problem prevention: hardly a low-hanging fruit. Participants’ experiences of the skills training were positive overall. Conclusions: Various aspects of the skills-training were appreciated by managers and HR-officers, including insight of prevalence statistics and employer responsibilities. Participants emphasized the value of repeated skills training occasions for retaining knowledge. Future research may investigate further in what way skills training may affect managers’ willingness to engage in workplace alcohol prevention. Since the implementation of any policy had gone unnoticed to participants; a reason for which could be related to the notion of the existing policy as “good enough” in its current condition, implementation- and organizational issues, or a reluctance to address alcohol-related matters unless necessary; future research may focus on investigating in what manner alcohol policies are in fact utilized within-organizations.